Developing Mathematics Teaching Devices in the Topic of Trigonometry Based on Guided Discovery Teaching Method - Naufal Ishartono; Dwi Juniati; Agung Lukito (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2016)
This research is categorized as Research and Development (R D). As developed in this research is learning device that consists of lesson plan, student worksheet, and test. This research adopts ADDIE as a R D model that stands for Analysis, Design, Development, Implementation, and Evaluation. The aim of this study are to describe the development process and to produce trigonometry learning device based on guided discovery method for students of grade XI Natural Science, as well as determine the effectiveness of trigonometry learning process using Guided Discovery method. To produce the trigonometry learning device based on guided discovery method for students of grade XI Natural Science, so it requires a validation from the experts and a trial to determine its practicability and effectiveness. According to the result of data analysis, it can be concluded: (1) trigonometry learning device based on guided discovery method for students of grade XI Natural Science fulfills criterion of valid, effective and practically, and (2) trigonometry learning process based on guided discovery method is effective.